PENGARUH LITERASI KEUANGAN, GAYA HIDUP, LINGKUNGAN SOSIAL, DAN KONTROL DIRI TERHADAP PENGELOLAAN KEUANGAN MAHASISWA EKONOMI (STUDI KASUS PADA MAHASISWA STIE MALANGKUCECWARA) - Deccasari, Dwi Danesty; Janan, Suci Syifaun; Marli, Marli (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
Financial management is an effort made by an individual in designing activities related to the storage and control of funds and assets. This research was conducted with the aim of examining and analyzing the effect of financial literacy, lifestyle, social environment and self-control on student financial management. The method in this study was multistage sampling which produced primary data using a questionnaire, the respondents were 70 students. The collected data will be tested through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of this study indicate that financial literacy, lifestyle, self-control have a significant effect on student financial management, the social environment has no significant effect on student financial management.